Chemotaxis-driven assembly of endothelial barrier in a tumor-on-a-chip platform - Aung, Aereas (Lab Chip, 2016)
The integration of three-dimensional micropatterning with microfluidics provides a unique opportunity to create perfusable tissue constructs in vitro. Herein, we have used this approach to create a tumor-on-chip with endothelial barrier. Specifically, we photopatterned a mixture of endothelial cells and cancer spheroids within a gelatin methacrylate (GelMA) hydrogel inside of a microfluidic device. The differential motility of endothelial and cancer cells in response to a controlled morphogen gradient across the cell-laden network drove the migration of endothelial cells to the periphery while maintaining the cancer cells within the interior of the hydrogel. The resultant endothelial cell layer forming cell-cell contact via VE-Cadherin junctions was found to encompass the entire the GelMA hydrogel structure. Furthermore, we have also examined the potential of such tumor-on-a-chip system as a drug screening platform using Doxorubicin, a model cancer drug.